2015
DOI: 10.1590/bjpt-rbf.2014.0110
|View full text |Cite
|
Sign up to set email alerts
|

Measuring sports injuries on the pitch: a guide to use in practice

Abstract: Sports participation is a major ally for the promotion of physical activity. However, sports injuries are important adverse effects of sports participation and should be monitored in sports populations. The purpose of this paper is to review the basic concepts of injury monitoring and discuss the implementation of these concepts in practice. The aspects discussed are: (1) sports injury definition; (2) classification of sports injuries; (3) population at risk, prevalence, and incidence; (4) severity measures; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Studies on field hockey have employed different populations, used different definitions of injury, and applied different methods for recording such injuries, which also makes comparisons difficult. In sport, continuous athlete monitoring (ie, longitudinal data) is recommended to get the full spectrum of injuries in a determined setting . To the best of our knowledge, the study with the longest period of injury registration in field hockey (ie, 15 seasons) reported that 3.7 injuries per 1000 player‐practices and 7.9 injuries per 1000 player‐matches were sustained by collegiate women field hockey players .…”
Section: Discussionmentioning
confidence: 99%
“…Studies on field hockey have employed different populations, used different definitions of injury, and applied different methods for recording such injuries, which also makes comparisons difficult. In sport, continuous athlete monitoring (ie, longitudinal data) is recommended to get the full spectrum of injuries in a determined setting . To the best of our knowledge, the study with the longest period of injury registration in field hockey (ie, 15 seasons) reported that 3.7 injuries per 1000 player‐practices and 7.9 injuries per 1000 player‐matches were sustained by collegiate women field hockey players .…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence is the number of cases (individuals) who reported health complaints (illness, overuse or acute injury) in a defined population at a certain point in time (equation 1). 25 …”
Section: Methodsmentioning
confidence: 99%
“…Thereafter, the mean prevalence and its 95 % CI were calculated by summing all prevalences measured every 2 weeks, divided by the number of 2-week time-periods. The injury rate was calculated by dividing the number of RRIs by the sum of total running exposure in hours [ 18 , 30 ]. The number of RRIs was calculated based on the number of unique RRIs identified during the follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…running sessions not fully accomplished or completely missed due to RRIs) and/or medical attention [ 17 ]. Defining RRI based only on these consequences could underestimate the overall burden of RRIs, since minor injuries not resulting in such consequences would be neglected [ 18 , 19 ]. Also, to register overuse injuries accurately, one needs a long follow-up time including regular measurement intervals in order to chart the gradual onset and fluctuations of symptoms related to overuse RRIs [ 16 , 18 ].…”
Section: Introductionmentioning
confidence: 99%